ANALYSIS OF FAULT PATTERNS THAT CAUSE DESTRUCTIVE EARTHQUAKES IN MAINLAND WEST JAVA - Basid, Abdul; Maharani, Fadia Ainina Putri; Rusli, Rusli (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2024)
West Java is one of the provinces in Indonesia with a high level of seismicity. During August 2024 alone, there have been 134 earthquakes with 23 earthquakes centered on land. The high seismicity on land is caused by the many faults on the mainland of West Java. This paper presents the results of research on fault patterns in mainland West Java from earthquake data from 1953 - 2023. The data of this research was obtained from the USGS, BMKG, GFZ, IRIS and Global CMT websites. The selected data is an earthquake with a magnitude of ≥ 5 SR and a depth of ≤ 40 km with an area boundary of 5°85 ́- 8°13 ́S and 106°74 ́- 108°76 ́ E. Using the Focal Mechanism Method, it can be found that the fault pattern that causes earthquakes in West Java in 1953-2023 is 5 reverse fault, 2 Normal fault, and 1 Strike-slip Fault. The results of this research are expected to be used as material for the preparation of earthquake disaster mitigation in West Java.